Reporting note as a type of prosecutorial response in section of the functions of the prosecutor’s bodies - Kucheriavyi, Petro (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
This article is devoted to the review and analysis of the functions of the prosecutor’s office, and also to the study of such a document as a report prepared upon consideration of certain issues by the prosecutor’s office in the course of exercising its functions. The author analyses the peculiarities of the prosecutor’s office activity, which, along with exercising law enforcement functions, also exercises the function of control over other law enforcement agencies, in particular, through procedural guidance in criminal proceedings. The author examines the issue of correlation between the Constitution of Ukraine and the Law of Ukraine ‘On Public Prosecution’ in terms of defining the functions of the latter. In particular, the author establishes that this definition differs, since according to the Fundamental Law, the prosecutor’s office performs the task of public prosecution in court, and the specialised law stipulates that it supports the public prosecution in court. The next function of the prosecutor’s office defined by law is representation of the interests of the State or a citizen in court in those cases which are defined by the Law of Ukraine ‘On the Prosecutor’s Office’, as well as Chapter 12 of Section III of the Civil Procedure Code of Ukraine (on the so-called civil forfeiture), which has some differences with its wording in the Constitution of Ukraine. The author concludes that despite a fairly detailed explanation of this function in the relevant law, as well as the inherent difference between the interests of a citizen and the State, the discrepancy between the law and the Constitution of Ukraine in defining this function remains unclear. The functions of control over the compliance of bodies conducting operational and investigative activities, inquiries, pre-trial investigations with the legislation of Ukraine, as well as supervision over the execution of court decisions in criminal cases and other coercive measures related to the restriction of personal freedom of citizens, are effectively combined into a single function. The prosecutor’s office of Ukraine may issue instructions, orders and other organisational and administrative documents that create a legal mechanism for implementing joint decisions to achieve effective departmental control.